2010
DOI: 10.1111/j.1745-4514.2009.00288.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF POTASSIUM SORBATE AND MODIFIED ATMOSPHERE PACKAGING ON THE SHELF-LIFE EXTENSION OF SEER FISH (SCOMBEROMORUS COMMERSON)STEAKS DURING ICED STORAGE

Abstract: A study to evaluate the influence of potassium sorbate combined with modified atmosphere packaging (MAP) at 2C on the shelf‐life extension of seer fish (Scomberomorus commerson) steaks was made. The shelf life of 12 days in air pack was extended by 10 and 18 days in MAP and modified‐atmosphere‐packed seer fish pretreated with potassium sorbate, respectively. K value was not a suitable predictor of shelf life for seer fish. Potassium sorbate treatment showed further inhibition of total aerobic mesophilic count … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 51 publications
1
12
1
Order By: Relevance
“…At the limit of sensory acceptability, the levels of K value in samples respectively for CAP, CVP and MEVP were 81.27, 77.57 and 87.54%. The rejection levels of K value observed in the present study were lower to other observations given by Ozogul et al (2004) for sardines (90%) and Yesudhason et al (2010) for seer fish steaks (95%), whereas Ozogul et al (2008) recorded K value as 81% as the limit of acceptability in ice stored grouper. Manju et al (2007) reported that vacuum packaging is effective in controlling nucleotide degradation in pearl spot stored in ice.…”
Section: K Valuecontrasting
confidence: 93%
“…At the limit of sensory acceptability, the levels of K value in samples respectively for CAP, CVP and MEVP were 81.27, 77.57 and 87.54%. The rejection levels of K value observed in the present study were lower to other observations given by Ozogul et al (2004) for sardines (90%) and Yesudhason et al (2010) for seer fish steaks (95%), whereas Ozogul et al (2008) recorded K value as 81% as the limit of acceptability in ice stored grouper. Manju et al (2007) reported that vacuum packaging is effective in controlling nucleotide degradation in pearl spot stored in ice.…”
Section: K Valuecontrasting
confidence: 93%
“…We suppose that this significant reduction observed in TMA production might be due to the inhibitory effect of AUSN-4 on TMA producing bacteria. Yesudhason, Gopal, Ravishankar, Lalitha, and Ashok (2010) reported a high correlation between TMA-N value and total aerobic mesophilic bacterial count. The results of our present study support the above findings, in which a direct correlation was observed between the total heterotrophic microbial population and TMA-N content.…”
Section: Chemical Analysesmentioning
confidence: 94%
“…MAP combined with refrigeration showed positive effects on the quality of cod fillets, particularly when very fresh raw material is used (Bøknaes et al, 2000). Further, MAP has been found to increase the shelf-life of seer fish (Scomberomorus commerson) (Yesudhason et al, 2009(Yesudhason et al, , 2010, Mediterranean swordfish (Kykkidou et al, 2009) and tuna fish burgers (Carlino et al, 2009). However, no information is available in the literature on preservation of bluefin tuna fillets by MAP.…”
Section: Introductionmentioning
confidence: 99%